Основи методики дослідження циклічного електроспоживання у штатному режимі - Бідний, М.С.; Мелешко, О.О.; Щербак, Т.Л. (Моделювання та інформаційні технології, 2009)
In this article are presented a base methods for making theoretical, imitational and experimental researches in a state mode. Such foundations are used for creation knowledge bases of electroconsumtion for organizations.